2007
DOI: 10.1016/j.ijdevneu.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in BDNF protein levels in human serum: differences between autism cases and normal controls

Abstract: Accumulating evidence suggests the possible association between the concentrations of serum brain-derived neurotrophic factor (BDNF) and psychiatric disease with impaired brain development. Yet the reasons remain unclear. We therefore investigated the characteristics of serum BDNF as well as its age-related changes in healthy controls in comparison to autism cases. BDNF was gradually released from platelets at 4 degrees C, reached a maximal concentration after around 24 h, and remained stable until 42 h. At ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 35 publications
11
91
1
1
Order By: Relevance
“…Although this observation is in harmony with results from other studies showing high concentrations of BDNF in autistic children (26), in another study the opposite result is reported (27). The level of serum BDNF was investigated as well as its age-related changes in healthy controls in comparison to autistic subjects.…”
Section: Bdnfsupporting
confidence: 84%
See 2 more Smart Citations
“…Although this observation is in harmony with results from other studies showing high concentrations of BDNF in autistic children (26), in another study the opposite result is reported (27). The level of serum BDNF was investigated as well as its age-related changes in healthy controls in comparison to autistic subjects.…”
Section: Bdnfsupporting
confidence: 84%
“…It has been noted that there were not any age-related changes in the serum levels of BDNF as in other studies (27). In a population of Chinese children aged around 4 years the potential role of BDNF was explored (29).…”
Section: Bdnfmentioning
confidence: 96%
See 1 more Smart Citation
“…The antibodies used for capture and detection in the various assays may recognize different forms of the BDNF molecule and differences in dilution factors or developmental age of subjects at specimen collection are likely to influence results [Katoh-Semba et al, 2007;Nelson et al, 2006]. The Luminex bead-based assay used for BDNF determinations in our study is highly sensitive (o10 pg/mL), and serum levels in maternal mid-pregnancy specimens were similar to those reported previously [Lommatzsch et al, 2006], whereas the standard ELISA assay only measures down to the ng/mL range.…”
Section: Discussionmentioning
confidence: 99%
“…In the autism cases, mean levels were significantly lower in children between 0-9 ages compared to teenagers or adults, or to age-matched healthy controls, indicating a delayed BDNF increase with development. In the same study, circadian changes, but not seasonal changes, were found in serum levels of BDNF (Katoh-Semba et al 2007). There is a little number of studies that concentrated on CSF levels of neurotrophic factors.…”
Section: Neurotrophic Factorsmentioning
confidence: 74%